Attitudes of women in Sefikile to food garden cooperatives and permaculture methods for income production. - Pillay, Erushka (My University, 2014)
ABSTRACT This feasibility study was conducted in Sefikile, a rural community in the North West Province with a complex social background. It aimed to examine the willingness of the women of Sefikile to become involved in a cooperative food garden project using sustainable methods for food production and income security. A survey of the literature provided evidence that community engagement and participation are central to the success of such an initiative as failure to engage the community could negatively impact on its implementation. The methodology employed during this study was a qualitative survey using a cross sectional design and a non-probability purposive sample. The findings indicated that while the women were willing to become involved in a food garden cooperative, their main desire was to create other types of income generating activities such as pig and chicken farming and other small enterprises. (142)
MM 2013
Keywords: Agriculture, Cooperative,Community development,Community gardens,Collective farms,Women-- Economic conditions.